Fibrinogen and C-Reactive-Protein Variation in Mild and Severe Preeclampsia - SH Yazdani (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Preeclampsia is one of the most prevalent diseases in pregnancy that include proteinuria and hypertension and can be associated with morbidity and mortality in mother and neonate. Endothelial cell dysfunction and inflammation are considered to have a crucial role in the pathophysiologic mechanism of preeclampsia. A systemic inflammatory response involves both the immune system and the clotting and fibrinolytic system. The aim of this study was to determine the association of fibrinogen and C-reactive protein (CRP) with the severity of preeclampsia. METHODS: This cross-sectional study was performed on 44 normal pregnant women, 35 cases with mild preeclampsia and 19 cases with severe preeclampsia that referred to Shahid Yahyanejad hospital, Babol, Iran. All of patients were primigravida and single pregnancy, cases over the age of 15 and gestational age of 30 to 40 weeks. Patients didn receive betamethasone in last week. The diagnosis of preeclampsia is made whose blood pressure reaches 140/90 mmHg or greater with proteinuria (trace or greater in random urine samples). Blood sample were taken from all subjects to measure CRP and fibrinogen and send to single laboratory. Then the groups were compared.FINDINGS: The mean of CRP was significantly different in control (2.28±0.81) and mild preeclampsia group (4.91±5.99) (p=0.03), and there was not significant difference between control (2.28±0.81) and severe preeclampsia group (3.8±3.05). The mean of fibrinogen was not significantly different in control group (360.5±62.35) and mild preeclampsia (344.71±65.07) and severe preeclampsia groups (340.95±78.62). CONCLUSION: Results show that CRP increased in mild preeclampsia in comparison with control group but there was not significant difference between fibrinogen level in control group with mild and severe preeclampsia.